Fundamentals of motor vehicle technology - Hillier, V. A. W.; Coombes, Peter; Rodgers, David R. (Nelson Thornes Ltd, 2004)
Hillier's famous series of Motor Vehicle Technology texts have been completely revised and updated. Endorsed by the IMI, these three texts are an excellent resource for apprentices as well as trained professionals